1989
DOI: 10.1210/jcem-69-4-832
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Analysis at the Clonal Level of Infiltrating T Lymphocytes in Papillary Carcinoma of the Thyroid: Prevalence of Cytolytic T Cells with Natural Killer-Like or Lymphokine-Activated Killer Activity*

Abstract: We investigated the phenotype and function of thyroid tumor-, metastatic lymph node-, and peripheral blood-derived T lymphocytes of four patients with papillary thyroid cancer. Both phenotypic analysis of freshly isolated cells and clonal analysis, using a high efficiency cloning technique, were performed. For comparison, intrathyroid and peripheral blood T lymphocytes derived from patients with autoimmune thyroid diseases (Graves' disease and Hashimoto's thyroiditis) have been studied. In papillary cancer, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 19 publications
0
21
0
3
Order By: Relevance
“…Given the histopathologic similarities between CLT and HT, it might be assumed that a Fas‐induced mechanism exists in CLT that involves the neoplastic cells of PTC; if expression of Fas is induced in the neoplastic cells of PTC, Fas ligand might enhance apoptosis in PTC via Fas . It is postulated that the infiltrated lymphocytes in patients with PTC are likely to be cytotoxic T cells with natural killer or lymphokine‐associated killer activity that act as carcinoma cell killers and secrete cytokines, such as interleukin‐1, that suppress carcinoma cell growth . Therefore, both humoral and cytotoxic T‐cell‐mediated destruction involved in autoimmune thyroid disorders may have a direct or indirect effect on PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Given the histopathologic similarities between CLT and HT, it might be assumed that a Fas‐induced mechanism exists in CLT that involves the neoplastic cells of PTC; if expression of Fas is induced in the neoplastic cells of PTC, Fas ligand might enhance apoptosis in PTC via Fas . It is postulated that the infiltrated lymphocytes in patients with PTC are likely to be cytotoxic T cells with natural killer or lymphokine‐associated killer activity that act as carcinoma cell killers and secrete cytokines, such as interleukin‐1, that suppress carcinoma cell growth . Therefore, both humoral and cytotoxic T‐cell‐mediated destruction involved in autoimmune thyroid disorders may have a direct or indirect effect on PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Bagnasco et al (22) reported a higher proportion of cytotoxic T cells with natural killer (NK)-like or lymphokine-activated killer activity in PTC infiltrating T cells compared to those occurring in autoimmune thyroid disorders (Hashimoto's thyroiditis and Graves' disease). In addition to the primarily cell-mediated inflammatory reaction observed in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cytokines such as interleukin-1 suppress carcinoma cell growth indirectly. 21,22 The autoimmunization process associated with Hashimoto's thyroiditis is associated with antigenproducing B lymphocytes, cytotoxic T cells, and macrophages Table 4. Lymph node metastasis according to Hashimoto's thyroiditis stratified by preoperative TSH Level.…”
Section: Discussionmentioning
confidence: 99%